High School Students’ Subjective Well-being: The Role of Life Purpose and Academic Identity - Sharma, Gitima; Yukhymenko-Lescroart, Mariya (Journal of Interdisciplinary Studies in Education, 2023)
The aim of this study was to investigate the relationships between high school students’ subjective well-being, academic identity, and sense of purpose in life. Specifically, this study examined the extent to which student subjective well-being can be predicted by sense of purpose in life directly and indirectly via academic identity. Two hundred and thirty-four high school students participated in the study. Findings showed that academic identity predicted all four dimensions of students’ subjective well-being. In relation to life purpose, findings showed that two dimensions of awakening to purpose and altruistic purpose were relevant to students’ subjective well-being. Particularly, students with altruistic purposes reported a more central role of academic identity in their sense of self and, in turn, reported greater satisfaction and joy of learning. Implications for future research and practice are discussed.